Potensi farmakologi Kasumba Turatea (Carthamus tinctorius L.) sebagai antibakteri - Lismayana Hansur; Ami Febriza; Dito Anurogo; Dara Ugi Aras; Endah Dwijayanti (MEDICINUS, 2024)
Kasumba turatea (Carthamus tinctorius L.) is a plant that has been used as traditional medicine in South Sulawesi. Themain component of C. tinctorius L. flowers is hydroxysafflor yellow A, which functions as an anti-inflammatory, antioxidant,and platelet aggregation inhibitor. This review highlights pharmacological potential of C. tinctorius L. as an antibacterialagent. The method involves a literature review from various databases such as PubMed, Google Scholar, and Scopus. Theresults show that C. tinctorius L. extracts are effective against various pathogenic bacteria such as Listeria monocytogenes,Streptococcus iniae, Staphylococcus aureus, and Escherichia coli. Bioactive compounds like carthamin, phenolics, and flavonoids exhibit significant antibacterial activity. Additionally, C. tinctorius L. extracts also show potential as anthelminticand antioxidant agents. Further research is required to isolate and characterize specific bioactive compounds, followed by in vivo validation and clinical study to confirm their efficacy as well as safety.